Answer:
y = 5(x² - 2) - 3
Step-by-step explanation:
In y = a(x² - b) + c, a is the stretch factor, -b is the horizontal, and c is the vertical
You did not give us the parent function, so I am going to assume it is y = x²
y = x²
3 units down means the function will be moved 3 units down, so it will look like:
y = (x²) - 3
Shifted 2 units to the right will result in a -2, so we add that in:
y = (x² - 2) - 3
The stretch factor is 5, which goes in front of everything else, multiplying the quadratic,
y = 5(x² - 2) - 3
Have a nice day!
I hope this is what you are looking for, but if not - comment! I will edit and update my answer accordingly. (ノ^∇^)
- Heather